1993
DOI: 10.2118/19114-pa
|View full text |Cite
|
Sign up to set email alerts
|

WAG May Improve Gas-Condensate Recovery

Abstract: This paper shows that the water-alternating-gas (WAG) process may improve sweep efficiency and gas-condensate recovery compared with continuous cycling in highly stratified reservoirs. The study used extensive numerical simulation to investigate the sensitivity of the process to several variables, including reservoir layering, permeability, relative permeability, capillary pressure, and trapped gas. The process mechanics were confirmed by laboratory displacements in layered core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Some researchers have suggested that the magnitude of the water relative permeability endpoint has only a small effect on WAG recovery. 45 Gas relative permeabilities measured under three-phase flow conditions with CO 2 are much lower than with N 2 . This could result in lower total mobility and lower injectivity than would be predicted if nitrogen relative permeability data were used to calibrate the simulator.…”
Section: Reservoir Heterogeneity 4 Capillary Forces 5 Dynamics Of Wmentioning
confidence: 91%
See 2 more Smart Citations
“…Some researchers have suggested that the magnitude of the water relative permeability endpoint has only a small effect on WAG recovery. 45 Gas relative permeabilities measured under three-phase flow conditions with CO 2 are much lower than with N 2 . This could result in lower total mobility and lower injectivity than would be predicted if nitrogen relative permeability data were used to calibrate the simulator.…”
Section: Reservoir Heterogeneity 4 Capillary Forces 5 Dynamics Of Wmentioning
confidence: 91%
“…Recently studies 44,45 have been conducted that show that the use of the WAG processes in gas condensate recovery may improve sweep efficiency. WAG is effective in recovering significantly more condensate with less injected gas than continuous gas injection and could substantially improve economics.…”
Section: Gas Reservoir Uses Of Wagmentioning
confidence: 99%
See 1 more Smart Citation
“…Abel et al (1970) observed that the higher the injection pressure is, the higher the recovery of condensate oil will be. Cullick et al (1993) reported that gas-water alternating injection can significantly improve the recovery of stratified condensate gas reservoir contrasted to continuous injection if the high permeability strips exist. Edmond (2006) showed that CO 2 injection is very effective to improve the recovery of condensate gas reservoir by reducing the surface tension.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed et al(1998) analyzed the effectiveness of lean gas, nitrogen and carbon dioxide in a "Huff and Puff" injection manner for condensate removal concluding that Huff and Puff injection was most productive when done before the maximum liquid drop out is reached. Cullick et al (1993) performed some simulation and experimental work on the effectiveness of water alternating gas (WAG) for improving deliverability in condensate reservoirs.…”
Section: Introductionmentioning
confidence: 99%